2007
DOI: 10.1373/clinchem.2006.081679
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of ELISA and xMAP Technology for Analysis of Amyloid β42 and Tau Proteins

Abstract: ELISA were observed for each biomarker, indicating that a constant correction factor cannot be applied to recalculate xMAP results into ELISA results. When a combination of CSF markers was used, the sensitivity, specificity, and area under the ROC curves for xMAP assays and ELISAs were not significantly different in differentiating AD patients from vascular dementia patients and controls. Conclusions: A constant conversion factor cannot be used successfully to recalculate results obtained with xMAP assays to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
57
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 27 publications
(19 reference statements)
9
57
0
4
Order By: Relevance
“…All analyses were performed in the RUNMC with an ELISA as described previously (all from Innogenetics NV, Gent, Belgium). 18 We performed standard CSF analysis, including leukocyte count, erythrocyte count, total protein, and glucose. A leucocyte count #4/mL, red blood cells ,1,500/mL, total protein ,700 mg/L, and glucose ,4.3 mmol/L were considered normal.…”
mentioning
confidence: 99%
“…All analyses were performed in the RUNMC with an ELISA as described previously (all from Innogenetics NV, Gent, Belgium). 18 We performed standard CSF analysis, including leukocyte count, erythrocyte count, total protein, and glucose. A leucocyte count #4/mL, red blood cells ,1,500/mL, total protein ,700 mg/L, and glucose ,4.3 mmol/L were considered normal.…”
mentioning
confidence: 99%
“…The discrepancies between the xMAP and ELISA methods could be attributed to differences in antigen coating, reaction principles, and procedure (29). Our results showed that ELISA was better for anti-EBV IgA and that the xMAP assay was better for IgG-EA-D for distinguishing NPC patients from healthy populations, although the reasons remain unclear.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, more than 100 distinct reactions can be carried out simultaneously on the various beads in one tube, in which the individual bead is identified by a Luminex 100 or 200 instrument (11,12,21). Obviously, the xMAP assay requires a smaller sample volume, fewer procedure steps, and less total reaction time than tradi-tional ELISA (27,29). Moreover, the xMAP technology is highly reproducible because each result is the mean for ϳ100 readings (28).…”
mentioning
confidence: 99%
“…This quantification is based the recognition of the epitopes corresponding to the C-terminus amino acids of Aβ 1-40 and Aβ 1-42 using, respectively, the 2G3 and 21F12 antibodies. Recently, new multiplex immunoassays detecting multiples isoforms of Aβ peptides (1-38, 1-40 and 1-42) have been developed using Meso Scale Discovery (MSD) and Luminex platforms [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%